2016
DOI: 10.1002/dev.21479
|View full text |Cite
|
Sign up to set email alerts
|

The “when” and the “where” of single‐trial allocentric spatial memory performance in young children: Insights into the development of episodic memory

Abstract: Allocentric spatial memory, "where" with respect to the surrounding environment, is one of the three fundamental components of episodic memory: what, where, when. Whereas basic allocentric spatial memory abilities are reliably observed in children after 2 years of age, coinciding with the offset of infantile amnesia, the resolution of allocentric spatial memory acquired over repeated trials improves from 2 to 4 years of age. Here, we first show that single-trial allocentric spatial memory performance improves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 43 publications
(93 reference statements)
2
25
0
Order By: Relevance
“…Across the entire sample, retention of temporal information, but not spatial information, uniquely declined from the recall to the future condition. This is consistent with research showing that children retain spatial information better than temporal information (Lee, Wendelken, Bunge, & Ghetti, 2016;Picard, Cousin, Guillery-Girard, Eustache, & Piolino, 2012) and experience unique difficulty at integrating temporal information in future-oriented actions (Burns & Russell, 2016;Hayne & Imuta, 2011;Loucks, Mutschler, & Meltzoff, 2017;McCormack & Hanley, 2011;Ribordy Lambert, Lavenex, & Banta Lavenex, 2017). It is remarkable that declines were observed when children could have "simply" reproduced the same action sequences that were enacted in response to the recall task only a few moments earlier.…”
Section: Discussionsupporting
confidence: 88%
“…Across the entire sample, retention of temporal information, but not spatial information, uniquely declined from the recall to the future condition. This is consistent with research showing that children retain spatial information better than temporal information (Lee, Wendelken, Bunge, & Ghetti, 2016;Picard, Cousin, Guillery-Girard, Eustache, & Piolino, 2012) and experience unique difficulty at integrating temporal information in future-oriented actions (Burns & Russell, 2016;Hayne & Imuta, 2011;Loucks, Mutschler, & Meltzoff, 2017;McCormack & Hanley, 2011;Ribordy Lambert, Lavenex, & Banta Lavenex, 2017). It is remarkable that declines were observed when children could have "simply" reproduced the same action sequences that were enacted in response to the recall task only a few moments earlier.…”
Section: Discussionsupporting
confidence: 88%
“…These results suggested that individuals with DS are capable of response learning from 16 months of age. Note that the same participants were tested on a place learning task, but consistent with the results of other studies describing the emergence of place learning between 21 and 25 months of age ( Newcombe et al, 1998 ; Ribordy Lambert et al, 2013 ; Ribordy Lambert et al, 2015 ), neither DS nor TD children were able to exhibit reliable place learning. The inability of individuals with DS to exhibit place learning was thus inconclusive.…”
Section: Introductionsupporting
confidence: 72%
“…cues was found in 11 articles (Gouteux & Spelke, 2001;Hermer-Vazquez, Moffet, & Munkholm, 2001; Ribordy, Jab es, Banta Lavenex, & Lavenex, 2013;Ribordy Lambert, Lavenex, & Banta Lavenex, 2017;Schmuckler & Jewell, 2007;Twyman, Friedman, & Spetch, 2007;van den Brink & Janzen, 2013;Vasilyeva & Bowers, 2006;Waismeyer & Jacobs, 2013). Twenty-two studies used proximal cues (Crowther et al, 2000;Gouteux & Spelke, 2001;Hermer-Vazquez et al, 2001;Huttenlocher & Vasilyeva, 2003;Kaufman & Needham, 2011;Learmonth et al, 2002Learmonth et al, , 2001Lee, Sovrano, et al, 2012;Lee & Spelke, 2010Lee, Winkler-Rhoades, et al, 2012;Lew et al, , 2006Lourenco et al, 2009;Lourenco & Cabrera, 2015;Nardini, Atkinson, et al, 2008;Nardini, Jones, et al, 2008;Newcombe et al, 2010;Ruggiero et al, 2016;Twyman et al, 2007;Yousif & Lourenco, 2017), while those using both proximal and distal cues in the tasks were 14 (Bullens, Nardini, et al, 2010;Bullens et al, 2011;Hupbach & Nadel, 2005;Learmonth et al, 2008;Leplow et al, 2003;Nardini et al, 2006;Rodrigue...…”
Section: Yousif Andmentioning
confidence: 99%
“…The proximal cues usually used in the studies were traffic cones (Bullens, Nardini et al, 2010), small colored or geometrical wood pieces (Bullens, Klugkist, & Postma, 2011;Ruggiero et al, 2016), paper lanterns (Crowther et al, 2000;, rhomboid tabletop (Hupbach & Nadel, 2005), cylindrical figures (Huttenlocher & Vasilyeva, 2003), colored paper squares (Learmonth et al, 2002), bookshelves and doors (Learmonth et al, 2001), columns (Lee, Winkler-Rhoades, et al, 2012), sculpture objects (Lew et al 2006), led light figures (Nardini, Jones, et al, 2008), object pictures , toys (Waismeyer & Jacobs, 2013), colored or geometrically printed walls or curtains (Learmonth et al, 2008;Lourenco, Addy, & Huttenlocher, 2009;Lourenco & Cabrera, 2015;Nardini, Atkinson, & Burgess, 2008;Twyman et al, 2007), plastic boxes or colored glasses (Learmonth et al, 2001;Schmuckler & Jewell, 2007;, as well as the use of the environment's own geometry as an allocentric cue Lee, Sovrano, & Spelke, 2012: Yousif & Lourenco, 2017. The distal cues used were shaped neon lights (Bullens, Nardini et al, 2010), colored papers (Bullens et al, 2011), colored curtains and cardboards (Gouteux & Spelke, 2001;Hupbach & Nadel, 2005), and furniture Ribordy et al, 2013;Ribordy Lambert et al, 2017;Vasilyeva & Bowers, 2006). Studies assessing performance in outdoor tasks normally used distal cues, usually trees, swings, benches, water towers, and so forth (Mandolesi et al, 2009;.…”
Section: Yousif Andmentioning
confidence: 99%